2014
DOI: 10.1126/science.1256930
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor heterogeneity in localized lung adenocarcinomas delineated by multiregion sequencing

Abstract: Cancers are composed of populations of cells with distinct molecular and phenotypic features, a phenomenon termed intra-tumor heterogeneity (ITH). ITH in lung cancers has not been well studied. We applied multi-region whole exome sequencing (WES) on 11 localized lung adenocarcinomas. All tumors showed clear evidence of ITH. On average, 76% of all mutations and 20/21 known cancer gene mutations were identified in all regions of individual tumors suggesting single-region sequencing may be adequate to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
828
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 849 publications
(900 citation statements)
references
References 46 publications
(29 reference statements)
66
828
3
3
Order By: Relevance
“…The coexistence of subpopulations of tumor cells with distinct phenotypic and functional properties within the same tumor points to the existence of uncharted cellular interactions or pathways that contribute to tumor growth and dissemination. Studies in renal cell carcinoma (45) and lung adenocarcinoma (46) have revealed substantial intratumoral heterogeneity as a result of subclonal driver events. Additional studies establish that interactions between genetically distinct subclones of tumor cells are necessary for maintaining tumor heterogeneity (47) and that even minor subpopulations of tumor cells may promote bulk tumor growth via mechanisms of non-cell-autonomous stimulation (48).…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of subpopulations of tumor cells with distinct phenotypic and functional properties within the same tumor points to the existence of uncharted cellular interactions or pathways that contribute to tumor growth and dissemination. Studies in renal cell carcinoma (45) and lung adenocarcinoma (46) have revealed substantial intratumoral heterogeneity as a result of subclonal driver events. Additional studies establish that interactions between genetically distinct subclones of tumor cells are necessary for maintaining tumor heterogeneity (47) and that even minor subpopulations of tumor cells may promote bulk tumor growth via mechanisms of non-cell-autonomous stimulation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations are present in all cells and they are the consequence of multiple mutational processes, including the intrinsic slight infidelity of the DNA replication machinery, exogenous or endogenous mutagen exposures, and enzymatic modification of DNA and, at present, they have been classified into 30 signatures 35, 36, 37, 38. The nucleotide substitutions in those tumors were characterized as C>T from ultraviolet light (signature 7)23 and C>A from smoking (signature 4) 19, 20. Both substitutions were observed as founder events.…”
Section: General Components Of Ithmentioning
confidence: 99%
“…In addition, low‐grade glioma showed an exacerbated diversity in ITH after treatment with the alkylating agent temozolomide 39. In non‐small‐cell lung cancers (NSCLC) and bladder cancer, the apolipoprotein B mRNA editing enzyme, catalytic polypeptide‐like (APOBEC) family of proteins was associated with fostering many subclones (signature 2) 19, 20, 40…”
Section: General Components Of Ithmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other solid malignancies, the amount of genetic ITH detected for ESCC can be regarded as modest: for example, the amount of ITH seems comparable to lung cancer, where 76% of common mutations were reported, but far lower than clear cell renal carcinoma, where 67% of non-synonymous somatic mutations were subclonal (3,9).…”
mentioning
confidence: 99%